The Effectiveness Combination of Blended Learning and Flipped Classroom with Edmodo as a Digital Media Innovation for Learning From Home - Purba, Ramen Antonov (Journal of Education Technology, 2021)
Covid-19 causes transformation. Educational institutions prepare teaching media that can be accessed online. Such as WhatsApp, Instagram, google meet, google classroom, and zoom. The media is not yet the right solution. This study aims to analyze the effectiveness of the blended learning model using the flipped classroom method with Edmodo. Quasi research and experimentation. Data analysis with the descriptive pattern. The technique of collecting data is by direct observation, filling out questionnaires, and carrying out tests. Analyzing information is carrying out initial knowledge testing, hypothesis testing, and analyzing learning activities. Through t-test, normality, homogeneity, and comparative to see the effectiveness of the combination of blended learning and flipped classroom with Edmodo. The research subjects were 32 students. The result is that the blended learning model using the flipped classroom method with Edmodo is effective as a medium for learning the context of learning from home. There are differences in the value and quality of individuals in learning. Value using WhatsApp, Instagram, google meet, google classroom, and Zoom 63.89. Using a combination of blended learning and flipped classroom with Edmodo 80.56. With the category of learning activities at the level of 92.1%. The blended learning model with the flipped classroom method with Edmodo is effectively used. There is an increase in learning activities that have a positive impact on the value and quality of individual learning activities. The combination of the three is a new digital media innovation for learning.